HUBUNGAN ASUPAN SERAT DENGAN STATUS GIZI DAN PROFIL LIPID DARAH PADA ORANG DEWASA DISLIPIDEMIA - Lilik Kustiyah; Maya Utami Widhianti; Mira Dewi (Jurnal Gizi dan Pangan, 2013)
The objective of this study was to analyze the association of fiber consumption with nutritional status and blood lipid profile in dyslipidemic adults. The design study was cross sectional survey involving 79 subjects. The results showed that there were significant correlations between energy intake with High Density Lipoprotein (HDL) cholesterol and total cholesterol, fat intake with BMI (Body Mass Index), and BMI with Low Density Lipoprotein (LDL) cholesterol and total cholesterol (p<0.05). There was no significant correlation between consumption of fiber with nutritional status and blood lipid profile (p>0.05). In conclusion, most of the dyslipidemia subjects were obese. Dyslipidemia subjects should keep their intake of energy and fat in recommended ranges in order not to be obese and keep the BMI in normal range to avoid abnormalities of blood lipid profile.